CEREBELLAR DYSARTHRIA: A COMPREHENSIVE ANALYSIS OF NEUROGENIC SPEECH DISORDER - Iminjonova Mokhichehra Alimardon qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ABSTRACT: Cerebellar dysarthria is a disorder of the articulatory, phonational, respiratory, and prosodic components of speech resulting from damage to the central and/or peripheral nervous system. This article examines the etiopathogenesis, clinical forms, differential diagnosis, and modern rehabilitation approaches of cerebellar dysarthria. The effectiveness of various treatment methods, such as speech therapy, assistive technologies, and pharmacotherapy, is analyzed based on scientific literature.